BENTUK LAGU MARS FKIP UNIVERSITAS PGRI PALEMBANG IRINGAN MUSIK FORMAT ORKESTRA - Silo Siswanto (Besaung : Jurnal Seni Desain dan Budaya, 2021)
The motto of PGRI Palembang University is that the campus advances with quality. Then a need for faculties to make a stragi in providing encouragement and motivation to the academic community to carry out the tri dharma of higher education. (FKIP) Palembang PGRI University through its highest leadership in the faculty gave a letter of assignment to work on the Mars song FKIP PGRI Palembang University to one of the music art lecturers in the performing arts education study program named Silo Siswanto, M.Sn. Then the Mars song was finished on July 23, 2018 and was launched on July 31, 2018 in the FKIP University of Palembang PGIP judicial event held at the Science Center building at the PGRI University in Palembang. Regarding the form in the Mars song, of course, this song has pieces of melody that are often known by the term phrases or musical sentences that make up the song. while the accompaniment music is arranged in an orchestra format. The formulation of the problem. (1) What is the form of Mars FKIP University PGRI Palembang song. (2) How is the accompaniment of Mars FKIP Palembang PGRI University music with orchestra format. The results of the discussion FKIP march song has a poly metric musical form where the antecedent phrase and consequent phrase do not have the same number of bars for example period C has 9 bars consisting of the phrase d 4 bars and the phrase e 5 bars.Keywords: Song Form, Mars Song, Orchestra